Experimental investigation of characteristics of pneumatic artificial muscles - Gyeviki, János; Sárosi, József; Véha, Antal; Toman, Péter (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
The characteristics of pneumatic artificial muscles (PAMs) make them very interesting for the development of robotic and prosthesis applications. The McKibben muscle is the most popular and is made commercially available by different companies. The aim of this research is to acquire as much information about the pneumatic artificial muscles as we can with our test-bed that was developed by us and to be able to adopt these muscles as a part of prosthesis. This paper presents the set-up constructed, and then describes some mechanical testing results for the pneumatic artificial muscles.